2020
DOI: 10.1002/anie.202003119
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Generation of 9‐Boratriptycene by Lewis Adduct Dissociation: Accessing a Non‐Planar Triarylborane

Abstract: A highly bent triarylborane, 9‐boratriptycene, was generated in solution by selective protodeboronation of the corresponding tetra‐aryl boron ate complex with the strong Brønsted acid HNTf2. The iptycene core confers enhanced Lewis acidity to 9‐boratriptycene, making it unique in terms of structure and reactivity. We studied the stereoelectronic properties of 9‐boratriptycene by quantifying its association with small N‐ and O‐centered Lewis bases, as well as with sterically hindered phosphines. The resultant L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 59 publications
(1 reference statement)
1
68
0
Order By: Relevance
“… M06‐2X/6–311G(d) gas phase fluoride ion affinities (FIA, Δ H 0 in kJ mol −1 ), affinities with ammonia and triphenylphosphine (Gibbs free energies, Δ G 0 in kJ mol −1 ), global (ω, in eV) and local (boron, ω B , in eV) electrophilicity indexes of the borane derivatives 9 a – d and 4 a – d . As a comparison, the corresponding affinities (in kJ mol −1 ) of B(C 6 F 5 ) 3 for F − (Δ H 0 ), NH 3 (Δ G 0 ) and PPh 3 (Δ G 0 ) are −466, −117 and −62 respectively while its global and local electrophilicity indexes are, respectively 2.79 eV and −1.23 eV [23] . In parenthesis are indicated the reorganization energies necessary for the borane to reach its final geometry in the Lewis adduct.…”
Section: Resultsmentioning
confidence: 99%
“… M06‐2X/6–311G(d) gas phase fluoride ion affinities (FIA, Δ H 0 in kJ mol −1 ), affinities with ammonia and triphenylphosphine (Gibbs free energies, Δ G 0 in kJ mol −1 ), global (ω, in eV) and local (boron, ω B , in eV) electrophilicity indexes of the borane derivatives 9 a – d and 4 a – d . As a comparison, the corresponding affinities (in kJ mol −1 ) of B(C 6 F 5 ) 3 for F − (Δ H 0 ), NH 3 (Δ G 0 ) and PPh 3 (Δ G 0 ) are −466, −117 and −62 respectively while its global and local electrophilicity indexes are, respectively 2.79 eV and −1.23 eV [23] . In parenthesis are indicated the reorganization energies necessary for the borane to reach its final geometry in the Lewis adduct.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 20 years later, the same group described the formation of BPh 3 upon heating different tetraarylborate salts to at least 200 °C [67] . Tetraarylborates are used on rare occasions to this day as valuable, alternative precursors to triarylboranes [68–70] …”
Section: Synthesis Of Symmetrically Substituted Triarylboranesmentioning
confidence: 99%
“…[67] Tetraarylborates are used on rare occasions to this day as valuable, alternative precursors to triarylboranes. [68][69][70] Based on this work, Brown et al re-synthesized tri-a-naphthylborane 10 as ar eference Lewis acid to estimate the Lewis base strength of primary,s econdary,a nd tertiary amines, [71] having slightly modified the synthesiso ft he triarylborane. To make the synthesis safer,B rown and co-workersu sed boron trifluoride etherate( BF 3 •OEt 2 )i nstead of gaseous boron trifluoride.…”
Section: Boron Trifluoride As the Boron Sourcementioning
confidence: 99%
“…3a-c,13 Mikhailov realized such a structural motif by the synthesis of 1-boraadamantane, 14,15 while Berionni et al released a non-planar 9-boratriptycene (D) by in situ protonolysis of corresponding borate-complexes [R4P][tBuC6H4-D] with HNTf2 in CH2Cl2 (Tf = O2SCF3). 16 In the resulting mixture, D is in an association-dissociation equilibrium with the weakly coordinating [NTf2]ion and was isolated in the form of its trapping products with various N-, P-, or O-centered Lewis bases. 17 Structural data from X-ray crystallography are not available for either free 1-boraadamantane or D. Gas-phase electron diffraction on 3-methyl-1-boraadamantane at 100 °C revealed that the B atom in the equilibrium structure has a (slightly) pyramidal configuration with Σ(C-B-C) = 349.4(4)° and av.…”
Section: Introductionmentioning
confidence: 99%